Yerel yönetimlerin gelirleri ve mali özerklik ilkesi - Yildirim, Ali (Hasan Kalyoncu Üniversitesi, 2022)
Ülkemizde Anayasanın 127. maddesine göre Belediye, İl Özel İdaresi ve Köy tüzel kişiliği yerel yönetim kuruluşları olarak kabul edilmektedir. İnsana en yakın özerk hizmet idaresi olan yerel yönetimlerin merkezi idare altında faaliyette bulunurken yaşadıkları en önemli sorun ekonomik özgürlüklerinin sınırlı olmasıdır. Mali özerkliği olmayanın idari özerkliği olamayacağından bu çalışmada Yerel Yönetimlerin Gelirleri ve Mali Özerklik İlkesi üzerinden sınırlı gelir kaynakları ve bu gelir kaynaklarının nasıl olabileceği incelenmiştir. Çalışmada Belediye, Büyükşehir Belediyesi, İl Özel İdaresi ve Köy için gelirler; öz gelirler, idareler arası transferler, borçlanmalar ve diğer gelirler olarak ayrı ayrı incelenmiştir. Anahtar Kelimeler: Yerel Yönetim, Mali Özerklik, Gelir, Belediye, Vergi

In our country, according to Article 127 of the Constitution, Municipality, Special Provincial Administration and Village legal entities are accepted as local government organizations. The most important problem faced by local governments, which are the closest autonomous service administration to people, while operating under the central administration is the limited economic freedoms. Since those who do not have financial autonomy cannot have administrative autonomy, in this study, limited income sources and how these income sources can be examined through the Revenues of Local Governments and the Principle of Financial Autonomy. In the study, revenues for the Municipality, Metropolitan Municipality, Special Provincial Administration and Village; own revenues, transfers between administrations, borrowings and other revenues.
Revenues of local governments and the principle of fiscal autonomy
Keywords: Hukuk; Law